The impact of liquidity and leverage on financial performance of public listed firms in Jordan - Mohammad Alshakhanbeh; Anwar Allah Pitchay; Md Aslam Mia; Rami Nairoukh; Mohamad Isa Abd Jalil (Human Resource Management Academic Research Society, 2024)
This study investigates the impact of liquidity and leverage on the financial performance of public listed service firms in Jordan, offering insights into financial management in emerging economies. Using data from 38 service companies listed on the Amman Stock Exchange (2011–2021), the analysis focuses on financial metrics such as Current Ratio (CR), Cash Ratio (CHR), Quick Ratio (QR), Short-Term Debt (SD), Long-Term Debt (LD), Debt to Equity (DTE), and Earnings Per Share (EPS). Partial Least Squares Structural Equation Modeling (PLS-SEM) with PLS-SMART 4.1 was employed to analyze the data. The findings reveal that liquidity, particularly CR and CHR, positively influences financial performance, supporting the Pecking Order and Agency Cost Theories, while QR shows no significant impact. High leverage, especially LD and DTE, negatively affects performance, though SD has a positive relationship with EPS, aligning with the Trade-Off Theory. Control variables like Capital Intensity and Firm Size also significantly influence EPS, while Trading Volume and Firm Age do not. The study is limited to Jordanian service firms, and the findings may not apply to other sectors or regions. This research contributes to understanding financial management practices in emerging economies, offering valuable guidance for policymakers and managers to enhance financial sustainability and competitiveness.